Needs and Possibilities of Development of the Macedonian Motorways - Slobodan Ognjenovic, Tamara Narezhnaya, Zlatko zafirovski, Ivana Nedevska (Springer, Cham, volume 692, 2017)
The road network has been compared to the human blood circulation since the beginning of its development, the analogy referring to both its function and its hierarchically arranged and branching structure. In other words, the balanced development and the coordinated function, starting from the main arteries (motorways) until to the capillary system (local roads) is a precondition to the overall rationality of the existence and development of the organism (the country) and its vital functions (e.-g economy).
Keywords: Roads Development, Road network Maintenance, Annual average daily traffic